The Relationship Between Stress and Bedtime Procrastination in Adolescents Addicted to Social Media - Silvira Nurrahmi; Rahayu Hardianti Utami (In Trend : International Journal of Trends in Global Psychological Science and Education, 2025)
Today's adolescents often have difficulty managing their sleep schedules, which can have a negative impact on their physical and mental health. One factor contributing to this behavior is social media addiction, which often leads to delayed bedtimes.This study aims to determine the relationship between stress and bedtime procrastination in adolescents addicted to social media. This study used a quantitative approach with a correlational method, involving 224 adolescents aged 13-18 years identified as having social media addiction through a purposive sampling technique. The research instruments used were the Bergen Social Media Scale (BSMAS)(a=0,94), the bedtime procrastination scale (BPS) (a=0,83), and the perceived stress scale (PSS) (a=0,96). Data analysis was performed using the non-parametric Spearman rank test due to non-normal distribution of the data using IBM SPSS 31, with a correlation coefficient (r) of 0.126 and a significance level of p = 0.060. The results of this study found no significant relationship between stress and bedtime procrastination.